Steam Generator for Hydrothermal Treatment of Agricultural Equipment - V. A. Gusarov; L. Yu. Yuferev (Сельскохозяйственные машины и технологии)
The paper highlights the importance of keeping the working surfaces of agricultural machinery clean and describes the existing modern equipment for its cleaning. (Research purpose) To develop a biofuel system for cleaning machines, equipment and tools in the field. It is proposed to apply a mobile steam generator using wood, chocks, straw and other agricultural waste as a fuel and capable of providing pressure of 5 kilograms per square centimeter and a temperature of 150 degrees Celsius. (Materials and methods) The paper describes the algorithm of the steam generator operation and presents its main technical characteristics and the design diagram. Theoretical calculations of the air consumption for the constant and adjustable air supply systems are provided. (Results and discussion) It has been established that one load of 8 kilograms of biofuel and 6 liters of water ensures 20-25 minutes of intense steam production. The steam generator was equipped with two systems for supplying air to the furnace, a safety valve for dumping steam at excess pressure. The boiler has a built-in superheater that ensures the necessary steam characteristics at the boiler outlet. (Conclusions) The developed steam generator reveals the following advantages: mobility, use of biofuel, a 20-25 minutes continuous supply of superheated steam at one load. The new unit is designed for long-term operation and it is capable of not only defrosting and cleaning a frozen manure conveyor, a manure trolley, a spreader, and loader working bodies, but also warming up larger agricultural machinery. It is also suitable for sanitizing seed harvesting and livestock equipment in the field.